Alone or with others: Experiments on evacuation decision making. (March 2021) - Cuesta, Arturo; Abreu, Orlando; Balboa, Adriana; Alvear, Daniel
Abstract: A common assumption is that the way occupants respond in fires will be significantly influenced by whether they are alone or with others. However, experimental evidence of this is limited. Here we compare the evacuation decision-making of isolated individuals vs individuals in small-groups of 5 and 12–13 members. Experiments reveal that large groups are significantly more efficient than smaller groups and individuals alone. We also find that social influence is determinant for exit choice behavior in individuals. The results are consistent with recent findings attesting to the positive/negative effects of the social influence during evacuation. Highlights: Individuals alone and with others are compared in evacuation experiments. Large groups perform better than small groups and isolated individuals. Social influence determines exit choice behaviour. Future research may focus on social ties and leadership behaviour.